2010
DOI: 10.4067/s0718-381x2010000100010
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Characteristics in Relation to the Need of Orthodontic Treatments in Children

Abstract: Malocclusion represents a public health problem in Chile. Government policies create preventive and interceptive programs for these conditions. Nevertheless, there are no uniform criteria for the selection of patients who need early treatment; the decision is made by a specialist during orthodontic treatment. Here, we propose the Index for Early Intervention (IEI) for early detection of malocclusions. We treat malocclusions with a simple interceptive treatment to minimize or eliminate the need for orthodontic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Index for preventive and Interceptive Orthodontic Needs (IPION) has been developed and tested to determine the treatment needs specifically in mixed dentition. However, studies found that it has limitations, as it lacks sensitivity, related to choosing cases specific for preventive or interceptive orthodontics ( 17 ). IOTN was used in the present study as the validity and reliability of this index has been verified in previous studies ( 18 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Index for preventive and Interceptive Orthodontic Needs (IPION) has been developed and tested to determine the treatment needs specifically in mixed dentition. However, studies found that it has limitations, as it lacks sensitivity, related to choosing cases specific for preventive or interceptive orthodontics ( 17 ). IOTN was used in the present study as the validity and reliability of this index has been verified in previous studies ( 18 , 19 , 20 ).…”
Section: Discussionmentioning
confidence: 99%